A systematic review of questionnaires assessing the psychological impact of COVID-19. (November 2021) - Voitsidis, Panteleimon; Kerasidou, Maria Dialechti; Nikopoulou, Aliki Vasiliki; Tsalikidis, Prodromos; Parlapani, Eleni; Holeva, Vasiliki; Diakogiannis, Ioannis
Highlights: The COVID-19 pandemic has led to the development of a significant number of psychometric scales. Most of the scales explore symptoms of stress, anxiety and fear. The scales tend to be brief and easy to administer. The tools that have been created provide acceptable psychometrics and are of adequate quality, despite the special circumstances caused by the pandemic. Abstract: The COVID-19 pandemic has led to a number of complications in everyday life, greatly affecting public health. Estimating its impact on mental health constitutes a priority issue. The current study aims to summarize the scales that have been specifically developed for this reason and are not adaptations of already existing scales. A comprehensive search was conducted by two reviewers during the period 28/09/2020–30/09–2020 in the following databases: PubMed, ScienceDirect, ScieLo, Mendeley, Google Scholar. A quality appraisal of the identified scales was made by three reviewers using the COSMIN checklist for methodological issues and the Terwee criteria for measurement properties. Our search strategy yielded a total of 855 results. Of these, 832 articles were excluded according to exclusion criteria, 23 were assessed for eligibility and 10 were finally included. These are presented in the text with additional useful information found separately. The identified scales tended to be quite short and examine stress, anxiety or fear. All studies were cross-sectional and the majority was conducted online. Most of them had a good Cronbach value (> 0.80) and adequate fit indices. It is however noted that the evaluation of their quality may be untimely due to relevant lack of data.